PENGARUH OPERATING CAPACITY, RASIO ARUS KAS OPERASI, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021) - Safitriawati, Tita; Astuti, Nita; Dongoran, Parlindungan; Widiarti, Aniek; Hartati, Sifa (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2023)
The research method used is quantitative and associative in nature. The sampling technique in this study was purposive sampling, so that a sample of 100 samples were obtained consisting of 20 transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data analysis technique used in this study is panel data regression using statistical software Eviews 12. The results of this study indicate that partially operating capacity using the total asset turnover ratio has a negative and significant effect on financial distress as evidenced by the results with the tcount 3.41 < ttable 1.66 with a probability value of 0.001 < 0.05. The operating cash flow ratio variable has a positive and significant effect on financial distress as evidenced by the tcount 2.84 > ttable 1.66 with a probability value 0.0058 < 0.05. Then the sales growth variable has no significant effect on financial distress as evidenced by the tcount -1.64 < ttable 1.66 and a probability 0.1043 > 0.05. Based on the results of simultaneous data regression analysis, it shows that the Fcount is 3.44 > Ftable 2.70 with a probability value of 0.000032 < 0.05, it can be concluded that operating capacity, operating cash flow ratio, and sales growth simultaneously they have an influence on financial distress. Keywords: Operating Capacity, Operating Cash Flow Ratio, Sales Growth and Financial Distress